Faktor-Faktor Yang Mempengaruhi Pelanggan Dalam Pemesanan Kamar Hotel Grand Savero Hotel Bogor Secara Online - Ziidani, Virginia; Sulistiono, Sulistiono; Pambudi, Arde (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
Tourists' desire to visit Indonesia needs to be accompanied by ease of accessibility, facilities offered and availability of accommodation facilities. Hotels are a form of accommodation that supports tourism activities, where the availability of hotels becomes a supporting facility for tourists visiting a country. And along with the growth of the world of Indonesian tourism, the history of hotels in Indonesia also plays a role in its success. The existence of hotels in Indonesia is of course very much needed in the tourism industry, considering that without adequate accommodation, it is impossible for tourists to want to visit. Increasing tourist visits is a promising business prospect for investors to set up hotels. This increasing hotel construction is due to an increase in demand for occupancy rates every year. The increase in hotel occupancy rates in all provinces across Indonesia is accompanied by the rapid development of the hotel industry. Apart from that, nowadays society is made easier by increasingly sophisticated technology, this means that tourists who want to travel or travel can do it easily using gadgets. Starting from ordering transportation tickets, accommodation, restaurants and so on. This research was conducted to find out what factors encourage customers to make reservations at the Grand Savero Hotel online. The technique used in this research is the method of filling out a questionnaire. The research results show that there are four factors that encourage customers to make hotel reservations online, namely discounts, convenience, seeing other customer reviews, not being able to come directly to the hotel, Keywords: Hotel room reservations, customer decisions, online travel agent